Exploring the role of 'RE' in early childhood education and care as a response to the PREVENT agenda in England. Issue 7 (7th June 2019) - Meehan, Catherine; Meehan, Patrick
ABSTRACT: By the time children are 8 years of age, their attitudes, values, identities and beliefs are shaped and becoming solidly formed. Early childhood educators are uniquely positioned in children's lives to promote positive values and beliefs and to foster authentic appreciation of difference. This important work is challenged by a discourse in wider society, based on fears of certain groups of people linked to extremism and terrorism. Recent policy and law changes in England require teachers to be gatekeepers and report concerns to authorities. Contextual discourse analysis was used as the methodology to identify themes within the policy and curriculum documents reviewed in paper. This paper presents a case for early childhood academics and educators to consider a rationale for how they can promote values of tolerance and compassion and highlight and celebrate a range of religious and cultural traditions, and in order to promote a deeper respect and understanding.